The relationships between urbanization and bird functional traits across the streetscape - Pena, João Carlos [UNESP]; Ovaskainen, Otso; MacGregor-Fors, Ian; Teixeira, Camila Palhares; Ribeiro, Milton Cezar [UNESP] (Elsevier, 2023)
The urbanization process leads to changes in bird communities’ taxonomic and functional compositions. Highly urbanized areas generally exhibit a reduced number of bird species sharing few functional traits. However, most urban bird studies focused on vegetation patches in temperate cities. In this study, we investigate how urban environmental attributes – noise, height of buildings, and urban vegetation characteristics – modulate species occurrences and the distribution of functional traits across the streetscape of a tropical metropolis. We predicted diverse trait-environment relationships, but that highly urbanized contexts (e.g., noisy streets with tall buildings) would be mostly occupied b,y a lower number of species sharing generalist traits. We also predicted to observe streets with similar community composition (profiles) shaped by environmental conditions and interspecific interactions. We applied hierarchical modelling of species communities as a flexible framework for analysis of community data. We observed that, increased noise exposure and reduced green cover were negatively related with species richness due to their negative relationships with most species’ occurrences. On the other hand, larger number of trees and higher proportion of green cover presented mostly positive relationships with occurrences, and thus with species richness. Throughout our streetscape, community composition was highly heterogeneous and similar conditions led to similar profiles. For example, noisy streets may favor the presence of omnivorous and large-bodied species, while wooded streets may allow for the presence of smaller-bodied forest specialist species that exploit lower vegetation strata. Our results indicate that streetscapes may have the potential to harbor functionally and taxonomically diverse bird communities.
Keywords: Bird morphological and life-history traits; Joint Species Distribution Models; Neotropical city; Urban landscape